GE_GERICHTE P/13358/2021 vom 8. Oktober 2021 - GE Cour de justice (2021)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;INFRACTIONS CONTRE L'HONNEUR;CALOMNIE;DIFFAMATION;INJURE;E-MAIL;INTERNET;FOR DE LA POURSUITE | CP.3; CP.8; CPP.310.al1.leta; CP.173; CP.174; CP.177